Studi Faktor Kualitas Resonansi Bunyi pada Pipa Organa Tertutup Menggunakan Panjang Efektif - Feri Iskandar; Yudhiakto Pramudya (Universitas Nurul Huda, 2025)
This study aims to improve the accuracy of resonance analysis in closed pipe resonance through the measurement of quality factor (Q) and effective air column length. The method employed involves an automated system based on Arduino, equipped with an HC-SR04 sensor to measure distance and a KY-037 sensor to detect sound amplitude, integrated with Python-based data analysis for determining the resonance frequency. The measurement results show that the use of effective length with tube radius correction and improved frequency determination methods can reduce error from 1.33% to 0.24%, as well as decrease the standard deviation from 0.45 cm to 0.37 cm. Furthermore, quality factor analysis indicates an increase in the average value from 20 to 31, suggesting that the implemented resonance system and analysis method provide more accurate results, despite increased variability. Overall, the system successfully delivers more precise measurements in the analysis of resonance characteristics in closed organ pipes, particularly in relation to energy dissipation.